2018
DOI: 10.1016/j.jtho.2018.05.013
|View full text |Cite
|
Sign up to set email alerts
|

PD-L1 Immunohistochemistry Comparability Study in Real-Life Clinical Samples: Results of Blueprint Phase 2 Project

Abstract: BP2 consolidates the analytical evidence for interchangeability of the 22C3, 28-8, and SP263 assays and lower sensitivity of the SP142 assay for determining tumor proportion score on TCs and demonstrates greater sensitivity of the 73-10 assay compared with that of the other assays.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

41
570
3
4

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 657 publications
(618 citation statements)
references
References 22 publications
41
570
3
4
Order By: Relevance
“…However, several studies, including our own, have previously shown that the PD‐L1 IHC results from whole sections and small materials (e.g. biopsy or TMA) are largely comparable . Therefore, TMA can serve as an affordable alternative in evaluating inter‐ and intraobserver agreement for PD‐L1 IHC in the research setting.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…However, several studies, including our own, have previously shown that the PD‐L1 IHC results from whole sections and small materials (e.g. biopsy or TMA) are largely comparable . Therefore, TMA can serve as an affordable alternative in evaluating inter‐ and intraobserver agreement for PD‐L1 IHC in the research setting.…”
Section: Discussionmentioning
confidence: 93%
“…Similarly, the ICC is lower for SP142 clone compared with the other three clones when evaluating raw positive TC or IC percentages, being 0.689–0.694 compared with 0.834–0.983 of ICC from the other three antibody clones. SP142 clone has been previously shown to preferentially stain IC with a significantly lower percentage of TC staining in NSCLC, UC and HSCC . As the evaluators have remained the same for all antibody clones, it is likely that the unique staining properties of the SP142 clone is the cause of variable PD‐L1 readout.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this issue of Histopathology , authors Downes and colleagues interrogate the reproducibility of PD‐L1 interpretation utilising four different assays, including the pembrolizumab companion diagnostic assay 22C3 (pharmDx), the atezolizumab assay utilising SP142 (Ventana/Roche, Tucson, AZ, USA), the durvalumab complementary diagnostic SP263 and a laboratory‐developed test utilising the E1L3N clone . Inter‐ and intra‐observer reproducibility and inter‐assay reproducibility for PD‐L1 immunohistochemistry has been studied extensively in NSCLC, but few studies have examined the performance of these tests in tumours outside the lung. Applying staining thresholds defined by clinical trials, as well as raw tumour and immune cell percentage positivity, the authors demonstrate substantial concordance between pathologists reviewing PD‐L1 staining of urothelial, breast and head and neck squamous carcinomas using the SP263, 22C3 and E1L3N tests.…”
mentioning
confidence: 99%